PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJARTERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PRODUKTIF PROGRAM KEAHLIAN ADMINISTRASI PERKANTORANDI SMA NEGERI 1 BOJONG KABUPATEN PURWAKARTA - Atikah Nur Hidayati, - (2012)
The Problems that were analyzed in this study is not optimal students achievement at office administration skill program in SMK Negeri I Bojong Kabupaten Purwakarta. Research study focused on the factors that affect academic achievement; namely facility learning and motivation to learn Principal issues revealed in this study is the effect of learning facilities for learning motivation, learning motivation influence learning achievement and learning facilities influence directly and indirectly on learning achievement at SMK Negeri 1 Bojong Kabupaten Purwakarta. Respondents in this study amounted to 1.5 people are students of class XTT Office Administration Skills Program at SMK Negeri l Bojong Kabupaten Purwakarta. The research method used is descriptive method verification Data collection techniques is by distributing a questionnaire using Likert scale model, which is analyzed with path analysis. The results showed that the state of learning facilities at SMK School 1 Bojong is perceived good, the results of respondents indicate that student motivation is good, student achievement in the subjects of productive skills Office Administration program at SMK Negeri l Bojong are in the good category Leaming facilities affect learning motivation, learning motivation affect learning achievement, learning facilities affect directly and indirectly through the motivation to the achievement. Suggestions put forward is the need for coJlaboration between teachers, schools, residents and local government to improve school facilities so as to encourage student motivation in order to improve learning achievement.